Colombia : Poverty Report, Volume 1. Main Report - World Bank (Washington, DC, 2013)
The report appraises the impact of economic development, or lack thereof, on the welfare of the Colombian population, and the poor in particular, over the last two decades, and, identifies priority areas for public policy action, vis-e-vis the most vulnerable groups. The welfare assessment covers three key areas - income, access to social services, and personal security, while it also compares welfare indicators between urban, and rural areas, and across other regional partitions. Questions are raised on the depths of poverty, and, on the Government's responsiveness to the incidence of poverty. Findings suggest that despite substantial long-term progress, a recent setback fostered an extreme urban poverty, and, although during the period social indicators reflect positive social development trends, homicide and domestic violence for the poor, and property crime for the non-poor have escalated to unprecedented rates, where the burden of crime is disproportionately borne by poor women. This violence disrupts the market economy, imposing a considerable psychological cost on those who are not directly victimized as well. Government actions nonetheless, show huge public expenditure efforts in social sectors, but with mixed results; therefore, the study addresses the imperative need for high economic growth to reverse poverty, through social programs prioritizing on childcare, health, and basic infrastructure. Likewise, an environment of increasing economic insecurity calls for valuable policy instruments, namely, safety-net programs, to enhance social protection.